Пиренейские сказки: [пер. с фр.] / пер. с фр. О. Кустовой ; рис. Ю. Бочкарева - Кустова О. (Детская литература, 1987)
1-2кл Экземпляры: (20170531) / Инвентарный номер: 18791 / Цена: 0.65 / Сис.шифр: 84(4/8) / Авт.знак: П 33 / ББК: 84(4Фра)